Advances in turbine materials, design and manufacturing proceedings ... - Charles Parsons turbine conference Tyne, UK 1997; Strang, A. [ed.]; Banks, W. M. [ed.]; Conroy, R. D. [ed.]; Goulette, M. J. [ed.] (London Institute Of Materials, 1997)
Proceedings of the Fourth International Charles Parsons Turbine Conference, with focus on Advances in Turbine Materials, Design and Manufacturing held on the 4-6 November 1997, at the Civic Centre, Newcastle-upon-Tyne, UK
Keywords: Turbines; Turbines -- Design and construction